Biosynthetic Machinery of Diterpene Pleuromutilin Isolated from Basidiomycete Fungi. (23rd October 2017) - Yamane, Momoka; Minami, Atsushi; Liu, Chengwei; Ozaki, Taro; Takeuchi, Ichiro; Tsukagoshi, Tae; Tokiwano, Tetsuo; Gomi, Katsuya; Oikawa, Hideaki
Abstract: The diterpene pleuromutilin is a ribosome‐targeting antibiotic isolated from basidiomycete fungi, such as Clitopilus pseudo‐pinsitus . The functional characterization of all biosynthetic enzymes involved in pleuromutilin biosynthesis is reported and a biosynthetic pathway proposed. In vitro enzymatic reactions and mutational analysis revealed that a labdane‐related diterpene synthase, Ple3, catalyzed two rounds of cyclization from geranylgeranyl diphosphate to premutilin possessing a characteristic 5–6–8‐tricyclic carbon skeleton. Biotransformation experiments utilizing Aspergillus oryzae transformants possessing modification enzyme genes allowed the biosynthetic pathway from premutilin to pleuromutilin to be proposed. The present study sets the stage for the enzymatic synthesis of natural products isolated from basidiomycete fungi, which are a prolific source of structurally diverse and biologically active terpenoids. Abstract : Uncovering the parts of a whole : The biosynthetic pathway of pleuromutilin has been elucidated by in vitro enzymatic reactions and biotransformation experiments. Labdane‐related diterpene synthase Ple3 and five modification enzymes, three cytochrome P450s (Ple156), a dehydrogenase (Ple7), and an acetyltransferase (Ple2), have been functionally characterized.